Implementasi Nilai-Nilai Dasar Perdamaian dalam Pembelajaran Pendidikan Pancasila dan Kewarganegaraan - Ruslan, Ruslan; Sanusi, Sanusi; Safitri, Widia (Universitas Negeri Malang, 2021)
This study aimed to analyze the fundamental values of peace education and the implementation of the fundamental values of peace in Pancasila and Citizenship Education learning and its obstacles. This study used a descriptive qualitative approach to find out and describe the meaning behind implementing the basic values of peace. The fundamental concept of peace education consisted of twelve values, namely: (a) self-acceptance, (b) prejudice, (c) ethnic differences, (d) religious differences, (e) gender differences, (f) differences in economic status, (g) group differences, (h) diversity, (i) conflict, (j) reject violence, (k) admit mistakes, (l) forgive. Implementing the fundamental values of peace in learning was done by modifying the Learning Implementation Plan, models, media, and teaching materials according to reality or factual nature. Barriers to the implementation of the basic values of peace in learning were related to the ability of teachers to understand the fundamental values of peace, the low interest in student learning, and the lack of facilities and infrastructure to support the learning process.